2014
DOI: 10.1371/journal.pone.0101796
|View full text |Cite
|
Sign up to set email alerts
|

The Road to Gold: Training and Peaking Characteristics in the Year Prior to a Gold Medal Endurance Performance

Abstract: PurposeTo describe training variations across the annual cycle in Olympic and World Champion endurance athletes, and determine whether these athletes used tapering strategies in line with recommendations in the literature.MethodsEleven elite XC skiers and biathletes (4 male; 28±1 yr, 85±5 mL. min−1. kg−1 , 7 female, 25±4 yr, 73±3 mL. min−1. kg−1 ) reported one year of day-to-day training leading up to the most successful competition of their career. Training data were divided into periodization and peaking pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
252
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(293 citation statements)
references
References 50 publications
(111 reference statements)
30
252
1
10
Order By: Relevance
“…1,2 The specific sessions prescribed (4 × 4, 4 × 8, and 4 × 16 min) here were chosen based on a previous investigation, 3 as well as descriptive data from high performance endurance athletes detailing typical training sessions. 12,13 The present data confirm our preliminary findings from a smaller betweengroups comparison 3 and suggest that the same session effort does not correspond to equivalent RPE and session RPE endpoints for different HIIT prescriptions. Equivalent session effort need not result in equivalent perceived exertion during, at the end of, or 30 minutes after different HIT prescriptions.…”
Section: Discussionsupporting
confidence: 74%
“…1,2 The specific sessions prescribed (4 × 4, 4 × 8, and 4 × 16 min) here were chosen based on a previous investigation, 3 as well as descriptive data from high performance endurance athletes detailing typical training sessions. 12,13 The present data confirm our preliminary findings from a smaller betweengroups comparison 3 and suggest that the same session effort does not correspond to equivalent RPE and session RPE endpoints for different HIIT prescriptions. Equivalent session effort need not result in equivalent perceived exertion during, at the end of, or 30 minutes after different HIT prescriptions.…”
Section: Discussionsupporting
confidence: 74%
“…Blood [la j ] was measured after 4.30 min, and RPE was determined at the end of each 5-min step using Borg_s 6-20 RPE scale (3 Values are presented as mean (SD). Intensity distribution and specific training are calculated as percent of endurance training, and distributed according to session goal/time in zonemethod (SG/TIZ) (33). Zone 1 = 60%-75% of HR peak ; zone 2 = 75%-85% of HR peak ; zone 3 = 85%-90% of HR peak ; zone 4 = 90%-95% of HR peak ; zone 5 = 95%-100% of HR peak .…”
Section: Testing Proceduresmentioning
confidence: 99%
“…In endurance sports, these include the duration and intensity of individual training sessions, the frequency of training sessions, and the organizational pattern of these stimulus variables over time. Recent descriptive studies of some of the world_s best endurance athletes have shown that successful athletes in cycling (14,25,35), running (1,2), and cross-country skiing (21,22,33) perform a high volume of low-intensity training (LIT) (defined as work eliciting a stable blood lactate concentration [la j ] of less than approximately 2 mmolIL j1 ) in addition to much smaller but substantial proportions of both moderate-intensity training (MIT) (2-4 mmolIL j1 blood lactate) and high-intensity training (HIT) (training above maximum lactate steady-state intensity [94 mmolIL j1 blood lactate]) throughout the preparation period. The majority of descriptive studies present a ''pyramidal'' training intensity distribution (TID), with high volume of LIT, substantial MIT, and less HIT, whereas a few studies suggest athletes to adopt a ''polarized'' TID (reduced volume of MIT, somewhat higher HIT), which have been proposed to give superior endurance adaptations (27,29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6(p140) Unfortunately, published studies reporting on the actual training programs of world-class Olympic-sport athletes are lacking in the sport-science literature, besides a few notable exceptions including examples on swimming, 7 rowing, 8 running, 9 triathlon, 10 cycling, 11 cross-country skiing, and biathlon. 12 Ever since Founding Editor David Pyne and I started the discussions to establish the International Journal of Sports Physiology and Performance back in late 2004, it was very clear to us that case studies reporting on the physiology, training, and/or performance characteristics of elite individuals should always have a place in the journal. This vision was stated explicitly in the September 2006 editorial.…”
Section: Sharpshooting In Sport Science and Elite Sports Trainingmentioning
confidence: 99%